Can Nigeria Debt Be Sustained in the Face of Increasing Debt Profile? - Agu , Osmond Chigozie; Asaolu, Adepoju Adeoba (EuroEconomica, 2023)
Nigeria debt profile has been increasing and creating an uncertainty in its sustainability. This study analyzed the sustainability of increasing debt profile in Nigeria from 1980 to 2021 using annual time series data. The study employed unit root, cointegration test and autoregressive distributed lag techniques in is analyses. The result shows that in the long-run, the debt stock-primary balance relationship was positive, indicating that there was sustainability, as the government’s response was encouraging. On the other hand, in the short-run, there was an inverse debt stock-primary balance relationship, showing that there was a debt swell, as government did not respond appropriately to the rising debt. This poses a risk to debt sustainability. It was therefore recommended that fiscal discipline should be upheld by the government by curtailing wasteful spending; it is economically profitable to invest in the real sectors of the economy. Sustainability has to be achieved by matching spending with revenues. Government should also look inwards for revenue generation through efficient tax collection. This will greatly reduce the burden of debt servicing by the government. Finally, government should endevour to increase her primary balances in the face of increased debt.